Adsorption of Cu on Epichlorohydrin-Modified Magnetic FeO Microspheres Prepared by One-Step Solvothermal Synthesis - Shiwei Xiao; Rong Liu; Jiping Ma; Fengxi Chen (Adsorption Science & Technology)
Monodisperse epichlorohydrin (ECH)-modified magnetic Fe 3 O 4 microspheres (Fe 3 O 4 –ECH-n, where n indicates the initial ECH-to-Fe molar ratio) were prepared by a one-step solvothermal method using mono-ethylene glycol. ECH was grafted onto the surface of Fe 3 O 4 microspheres by in situ dehydrochlorination and hydrolysis. The ECH-derived organic groups (e.g. 1, 2-dihydroxypropyl) provide surface functional sites for the adsorption of Cu 2+ on Fe 3 O 4 –ECH-n. The Fe 3 O 4 –ECH-0.8 microspheres were found to have the highest Cu 2+ adsorption capacity (17.5 mg/g), and were magnetically recoverable and reusable for Cu 2+ adsorption for at least seven times without significant loss in their adsorption capacity. The addition of 2.5 wt% of NaCl significantly enhanced its Cu 2+ adsorption (from 17.5 to 28.5 mg/g). The apparent activation energy of the adsorption process was 14.7 kJ mol −1 . The adsorption process was endothermic (ΔH° = 11.8 kJ mol −1 ) and resulted in an increase in the entropy (ΔS° = 56.7 J mol −1 K −1 ). The negative value of ΔG° ensures that the adsorption occurs spontaneously.